A Prediction for Teacher Commitment; Effects of Managerial Style, Burnout and Demographics - Gokhan Demirhan; Cemil Yucel (Research in Social Sciences and Technology- OpenED Network, 2016)
The Purpose of this study is to determine the effects of managerial style, teacher burnout and demographics on teacher commitment. In accordance with this aim, a quantitative casual research design was implemented. Data of the research were gathered from 280 primary school teacher, by a questionnaire including managerial style, teacher burnout, teacher commitment and teacher demographics forms. For each research questions, Hierarchical Linear Regression analysis was carried out. According to the findings, task oriented behaviors of principal, emotional exhaustion level of the teacher, self-inadequacy feelings of teacher, marital status and work time spending at the same school predicts teacher commitment significantly. On the other hand, human orientation, isolation level from work environment, physical burnout level, vocational burnout level, gender, professional experience, educational level and working status variables does not predicts teacher commitment.